RISK ANALYSIS OF ISLAMIC BANKING FINANCING BUSINESS IN INDONESIA 2014-2018 - Herlan Firmansyah; Mohamad Anton Athoillah (IAIN Manado, 2019)
The purpose of this article is to analyze business risk in Islamic banking financing in Indonesia. The method used in this study is a qualitative research method with a descriptive approach. The data used in this study are secondary data sourced from Sharia Banking Statistics (SBS). The conclusions of this article are ten business risks that must be managed by Islamic banks in carrying out their functions, namely financing risk, market risk, liquidity risk, operational risk, legal risk, reputation risk, strategic risk, compliance risk, yield risk, yield risk, and investment risk. Four business risks affect the profitability of Sharia Commercial Banks (BUS) in Indonesia, namely financing risk as measured by NPF, the rupiah exchange rate measures market risk against the USD and inflation, return NCD measures risk on total deposits and investment risk measured by the percentage potential loss profit-sharing financing for mudharabah and musyarakah investment portfolios.